Model Pembelajaran Kooperatif Co-Op Co-Op dengan Pendekatan Predict-Observe-Explain untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis - Maryanti, Sri (Desimal: Jurnal Matematika, 2018)
The purpose of this study was to find our whether cooperative learning model Co-Op Co-Op approach POE (predict-observe-explain) can increase the ability troubleshooting mathematical students. This research is a research Quasi Eksperimental Design and design researchers used  in this study is the design of the control group pretest-postest, with a technique random class. Hypothesis test used in this research is t-test. From the results of statistical tests showed that the value of t_hitung based on the calculation obtained t_hitung = 5.500869, and t_tabel = 2.001 so that t_hitung> t_tabel. So based on these calculation can be concluded that the model cooperative learning CO-Op Co-Op approach POE (predict-observe-explain) can increase the ability troubleshooting mathematical students.